Review and key to Russian Far East Lathrolestes (Hymenoptera, Ichneumonidae) - Reshchikov, Alexey (Zootaxa, 2012)
All members of the genus Lathrolestes Förster (Hymenoptera: Ichneumonidae) from Russian Far East are reviewed. Twelve new species of Lathrolestes are described from Russian Far East: L. anularius sp. nov., L. cruentocaudus sp. nov., L. fumipennis sp. nov., L. kasparyani sp. nov., L. kerzhneri sp. nov., L. levaya sp. nov., L. nigronitens sp. nov., L. palatynus sp. nov., L. pubescens sp. nov., L. sachalinensis sp. nov., L. sparsus sp. nov., L. tolstoyi sp. nov. An illustrated key to Russian Far East species is provided.